Long-term Follow-up of Canaliculotomies after Canaliculitis - Stucki, Vera C.; Demolli, Pashija; Kniestedt, Christoph; Frimmel, Sonja (Klinische Monatsblätter für Augenheilkunde, 2018)
Background Canaliculitis is often misdiagnosed. There are several conservative and surgical treatment options.Patients and Methods Retrospective analysis of 14 canaliculotomies in 10 patients with canaliculitis. The overall length of the surgically induced opening was measured and compared to the corresponding untreated lacrimal punctae. Lacrimal duct concrements were liberated and sent for microbiological and histological analysis. Patient satisfaction and relief of symptoms were documented as well as clinical findings.Results Mean age was 59 ± 10 years (36 – 73 years) with balanced gender distribution. Mean follow-up time was 13 ± 8 months (4 – 27 months). Canaliculotomy was performed on 12 out of 14 inflamed canaliculi; in 2 cases, 3-snip punctoplasty was sufficient. The surgically induced length of the cuts was 1.7 ± 0.9 mm (0.4 – 3.7 mm). In 13 out of 14 cases, macroscopic concrements were found intraoperatively and actinomyces was verified histologically. Nine patients were free of symptoms postoperatively, and one patient manifested markedly less epiphora.Conclusions The canaliculi remained open within the long-term follow-up period without any drawbacks to the lacrimal outflow. No recurrent infections were seen.
Keywords: canaliculitis; canaliculotomy; epiphora; Actinomyces